The CT-Imaging Location of Lumbar 3 Sympathetic Radiofrequency Thermocoagulation for Sympathetic-Related Diseases Therapy - Wang R; Gao Z; Ma L (Journal of Pain Research)
Ruxiang Wang,1,* Zhuoyue Gao,2,* Ling Ma1 1Department of Anesthesiology and Pain Medicine, Affiliated Hospital of Jiaxing University, Jiaxing, People’s Republic of China; 2Department of Anesthesiology, Daqing Oilfield General Hospital, Daqing, 163001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Ma, Email 1319108@qq.comPurpose: The location characteristic of the lumbar 3 sympathetic trunk under Computed Tomography (CT) was discovered through 106 cases, imaging analysis after successful lumbar 3 sympathetic radiofrequency thermocoagulation operations serving the clinic and reducing the operation time.Methods: There are 113 patients underwent bilateral L3 lumbar sympathetic thermal radiofrequency procedures in our hospital from January 2017 to January 2021, with 106 cases of successful procedure. Four operation image distances were measured: 1. The left/right distances between the needle tip (the location of needle tip was the sympathetic trunk at the same CT scan level) and the transverse process of the lumbar spine (D1l/D1r); 2. The left/right distances between the needle tip and the medial margin of the psoas major (D2l/D2r); 3. The left/right vertical distances between the needle tip and vertebral body (D3l/D3r); 4. The left/right vertical distances between ureter and vertebral body (D4l/D4r). The Perfusion Index (PI) and the plantar temperature were monitored and recorded before and after the treatment (the higher PI value and the plantar temperature indicated successful procedure). After the procedure, the patients were followed up one day, one week, two months and six months for satisfaction, complications and recurrences.Results: The left distance (D1l) from the needle tip to the transverse costal process being 4.444± 0.7668mm, longer than the right side (D1r, P< 0.001). The left distance (D2l) being 1.260± 0.4261mm longer than the right side (D2r, P=0.0039). The left distance (D3l) was 1.634± 0.2597mm longer than the right side (D3r, P< 0.0001). The D4l and D4r both having a long distance far from needle tips (P=0.665). Both the left and right temperature and PI increased have statistical significances after treatment (P< 0.0001). There were 2(1.77%) cases experiencing numbness of big thighs, and 9(7.96%) cases of compensatory hyperhidrosis, with only 3 (2.65%) cases reverting to the original state six months later.Conclusion: Lumbar sympathetic radiofrequency thermocoagulation is a valid treatment option for sympathetic-related disease in lower limbs, and based on our study data CT-guided percutaneous puncture lumbar sympathectomy can easy be proceed and gained more persistent effection, the left needle distance more deeper than the right side, the distance from the left side should be far from vertebral body than the right side. The distance between the needle body and the vertebral body on the left side is far away from the right side.Keywords: sympathetic, radiofrequency thermocoagulation, CT-guided